Filsafat Pendidikan Islam di Era AI: Integrasi Epistemologi dan Aksiologi Islam - Mahbubi, M (Prodi Pendidikan Keagamaan Islam, 2025)
The advancement of artificial intelligence (AI) has significantly transformed Islamic education, raising concerns in epistemology (the nature and sources of knowledge) and axiology (ethics and values). Islamic epistemology holds that knowledge originates from revelation, reason, and experience, whereas AI relies on big data and algorithms, questioning its validity and authority in Islamic education. This study aims to integrate Islamic epistemology and axiology into AI development to ensure ethical and responsible applications. A qualitative literature review was conducted, employing triangulation (TRT) to cross-examine sources and audit trail to ensure research transparency and reliability. The analysis explores the implications of AI in education from an Islamic philosophical perspective. The findings highlight the necessity of embedding maqashid syariah (Islamic objectives) into AI frameworks to preserve religious values, intellect, and morality. The study concludes that integrating Islamic philosophical principles in AI can create an ethically sound and beneficial digital learning ecosystem.